The choanal anatomy of the Sebecus icaeorhinus Simpson, 1937 and the variation of the palatine shape in notosuchians (Crocodyliformes, Mesoeucrocodylia). (November 2022) - Bravo, Gonzalo Gabriel; Pol, Diego; Armella, Matías Alberto; Gómez, Kevin
Abstract: Sebecidae is a clade of large carnivorous crocodyliforms that thrived in the Cenozoic and is the only lineage of the diverse and terrestrial group Notosuchia that survived the end-Cretaceous mass extinction event. Sebecus icaeorhinus is the best-known taxon from this clade, both in terms of its cranial and postcranial anatomy (known primarily from the holotype and specimen MPEF-PV 1776, respectively). Additional material represented by a partial skull (MMP 235) is the only specimen that has preserved a complete choanal region. We describe new information from this specimen based on an X-ray computed tomography and identify through comparisons with other taxa a large degree of variability in the palatal anatomy within Sebecidae, in particular in the shape and extension of the palatine (the bone that defines the anterior position and shape of the secondary choana). We quantify variation in the shape of the palatine bone of sebecids through a 2D morphogeometric analysis within the context of notosuchian crocodyliforms. Although traditional accounts of palatal evolution in crocodyliforms linked variation of this structure to the adaptation to the aquatic environment, our analysis allows recognition of eight palatine morphotypes among terrestrial crocodyliforms with very distinct paleoecological traits, including carnivorous, omnivorous, and possibly herbivorous taxa. Furthermore, we show that sebecids had a higher morphological disparity in the choanal region than other terrestrial groups of Notosuchia, underscoring the importance of this region for comparative, morphofunctional, and phylogenetic studies.